2016
DOI: 10.1080/2331186x.2016.1156242
|View full text |Cite
|
Sign up to set email alerts
|

‘Complex teaching realities’ and ‘deep rooted cultural traditions’: Barriers to the implementation and internalisation of formative assessment in China

Abstract: This article forms the first part of an Action Research project designed to incorporate formative assessment into the culture of learning of a bilingual school in Shanghai, China. It synthesises the empirical literature on formative assessment in China to establish some of the difficulties that teachers have faced in trying to incorporate this approach into their teaching. Some of the barriers include student and teacher resistance and notions of face (mianzi) which are also related to deeply held cultural scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…A second reason could be the significance of the CET-4/6 certificates at the societal context for employment and other practical purposes, as evidenced in this and other studies (Chen and May 2016;. The third and the most important reason, in the authors' view, resides with the established mindset and practice in the macrocontexts, such as the emphasis on examination and its results, the utilitarian uses of the results of the CHC ideology (Han and Yang 2001;Poole, 2016), the elevated status of English as an international language and acceptance of certificates as proof of one's English proficiency in the socio-political area, and the yet-to-establish alternative This parameter is set to zero because it is redundant assessment methods within the EFL discipline. In other words, the initiative itself has reduced stakes from the micro-context alone and from the external assessment only, whereas the stakes were still high with the internal assessment framework and remained untouched within the tri-layered macro-contexts.…”
Section: Discussionmentioning
confidence: 77%
“…A second reason could be the significance of the CET-4/6 certificates at the societal context for employment and other practical purposes, as evidenced in this and other studies (Chen and May 2016;. The third and the most important reason, in the authors' view, resides with the established mindset and practice in the macrocontexts, such as the emphasis on examination and its results, the utilitarian uses of the results of the CHC ideology (Han and Yang 2001;Poole, 2016), the elevated status of English as an international language and acceptance of certificates as proof of one's English proficiency in the socio-political area, and the yet-to-establish alternative This parameter is set to zero because it is redundant assessment methods within the EFL discipline. In other words, the initiative itself has reduced stakes from the micro-context alone and from the external assessment only, whereas the stakes were still high with the internal assessment framework and remained untouched within the tri-layered macro-contexts.…”
Section: Discussionmentioning
confidence: 77%
“…Yet, an intervention study in writing classes in Norway found that teachers must improve their assessment practices at each stage in the learning process and construct a systematic approach that enables teacher and students follows up the assessment outcomes for improving learning outcomes (Burner, 2014). Teachers are encouraged to not only focus on learners' linguistic development, but also focus on assessing learners' linguistic knowledge formatively; nevertheless, in this instance, many teachers have been found to be unaware of formative assessment procedures that can positively impact student learning (Poole, 2016).…”
Section: Formative Assessmentmentioning
confidence: 99%
“…I focus on bilingual learners learning English in an internationalised school in Shanghai, China in order to provide a specific instantiation of digital funds of identity. An internationalised school is defined as a national school that offers an international curriculum, typically the International Baccalaureate or Cambridge examinations (Poole, 2016a). These schools occupy an interesting metaphorical and ideological borderlands position between local and international curricula, cultural traditions, and power relations which suggest the existence of third spaces in which students negotiate hybrid identities.…”
Section: Funds Of Knowledge 20: Towards Digital Funds Of Identitymentioning
confidence: 99%